Impact of Gender and Location on Mathematical Thinking and Mathematics Achievement - Nepal, Binod (Journal of Advanced Academic Research, 2017)
Educational empowerment is taken as the most important indicator of national development. Students’ achievement is seen as the key to improve educational empowerment. So to enhance students’ achievement we should pay attention to achievements of overall subject of the secondary level, which is the base of further education. This paper aimed to find out the level of Mathematical Thinking and the Mathematics Achievement of the students of grade X in Nepal gender and location wise. Three districts Sindhupalchok, Kathmandu, Mahottari were selected as the study area. 400 students were selected as the sample. Mathematical Thinking Test and Mathematics Achievement Test were used as the instruments and data was analyzed using t-test. Finally, the study found out that there is no significance difference on the level of Mathematical Thinking and the Mathematics Achievement between male and female and there was another finding was that there is significant difference between rural and urban students on the level of Mathematical Thinking and Mathematics Achievement. These findings are applicable to improve teaching strategies and create new plans to make better performance of the students from rural areas. Journal of Advanced Academic Research, Vol. 3, No.3, 2016, page:11-21